Juvenile idiopathic arthritis with systemic onset with inflammatory bone lesions: two case reports of patients successfully treated with canakinumab and experience gained from literature - Ekaterina I. Alexeeva; Ekaterina I. Alexeeva; Ekaterina I. Alexeeva; Tatyana M. Dvoryakovskaya; Tatyana M. Dvoryakovskaya; Tatyana M. Dvoryakovskaya; Irina T. Tsulukiya; Natalia M. Kondrateva; Natalia M. Solomatina; Gleb V. Kondratiev; Luliia V. Peshekhonova; Mikhail M. Kostik (Frontiers Media S.A., 2023)
Non-bacterial osteomyelitis (NBO) is a rare chronic inflammatory bone disease related to immune system dysregulation. This disease belongs to a family of autoinflammatory diseases. It often coexists with other TNF-α-mediated immune-mediated diseases such as juvenile idiopathic arthritis (JIA) and inflammatory bowel diseases. Previously, interleukin-1-driven inflammation was described predominantly in monogenic cases of NBO, such as DIRA syndrome or Majeed syndrome. However, the association between NBO and JIA with systemic onset (soJIA) has not been described yet.Herein, we describe the cases of two patients with soJIA with inflammatory bone lesions wherein canakinumab (anti-interleukin-1β antibodies) caused remission. Case descriptionsPatient 1-A 6-month-old boy with typical soJIA suffered a destruction of the 7th to 9th ribs and the left pubic bone. Antibiotics, IVIG, and cyclosporine proved ineffective. Corticosteroids were effective, but due to the factor of corticosteroid dependence, which has some disadvantages, canakinumab with a dosage of 4 mg/kg was initiated every 4 weeks, which completely controlled the disease and allowed to taper corticosteroids.Patient 2-A 2-year-old girl developed chronic non-bacterial osteomyelitis of the 5th rib 2 months after taking corticosteroids prescribed for typical soJIA. She underwent surgical debridement removal, and several courses of antibiotics proved ineffective. She developed macrophage activation syndrome, following which anakinra was prescribed, which resulted in only temporary improvement. Therefore, this drug was switched to canakinumab, which caused corticosteroid-free remission.ConclusionThis is the first description of a rare association of soJIA with inflammatory bone lesions with the proven efficacy of IL-1 blockade. The association of two autoinflammatory conditions should indicate IL-1-driven mechanisms and a possible genetic basis. Follow-up genetic and functional studies are required to better understand the pathogenesis of such overlapping diseases.